2012
DOI: 10.1159/000341096
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hearing Results and Otological Complications of Nasopharyngeal Carcinoma Patients: Comparison between Treatment with Conventional Two-Dimensional Radiotherapy and Intensity-Modulated Radiotherapy

Abstract: Objective: To assess the long-term audiological outcome and otological complications of nasopharyngeal carcinoma patients who have received intensity-modulated radiotherapy (IMRT) versus conventional two-dimensional radiotherapy (2 DRT). Study Design: Prospective study on the audiological outcome and otological complications 5–9 years after radiotherapy. Methodology: Patients had pure-tone audiogram before radiotherapy and 5 years after radiotherapy. Otological examination was performed 5–9 years after radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The characteristics of the included studies are shown in Table . Most of the studies were prospective (16 of 21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are shown in Table . Most of the studies were prospective (16 of 21).…”
Section: Resultsmentioning
confidence: 99%
“…Various RT techniques were used in the studies included: 3D conformal, conventional, and intensity‐modulated radiation therapy (IMRT). In some studies, different treatment schedules were used . In 15 studies, the dose to the cochlea was measured, with mean cochlear dose varying from 10.56 to 69.6 Gray (Gy).…”
Section: Resultsmentioning
confidence: 99%
“…A recent long-term follow-up study of Tsang et al studied patients with nasopharyngeal cancer (NPC) treated with IMRT or conventional therapy on their long-term hearing status (56 ears) [ 21 ]. They concluded that there was a BC threshold shift of 16.1 dB at 4 kHz 5 years after IMRT treatment and that this deterioration, in general, could not be attributed to ageing alone.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many therapeutic agents including saliva substitutes [26], intensity-modulated radiotherapy [27,28], pilocarpine [29,30,31,32], acupuncture [33,34], and amifostine [35,36] had been available to alleviate radiation-induced xerostomia, but they rarely had curable effects or were even controversial regarding the safety of their use. So, the best method to treat postradiation xerostomia would be to choose preventive measures.…”
Section: Introductionmentioning
confidence: 99%